Lunnyu soils in the Lake Victoria basin of Uganda: Link to toposequence and soil type - Fungo B.; Grunwald S.; Tenywa M. M.; Vanlauwe B.; Nkedi-Kizza P. (African Journal of Environmental Economics and Management, 2020)
We compared the physico-chemical characteristics of Lunnyu soils using soil type and slope position in order to explain their variability in the Lake Victoria basin of Uganda. Lunnyu patches located on four different soil types (chromic lixisol, mollic gleysols and plinthic ferralsols) were selected. At each patch, the slope was divided into shoulder, back-slope and foot-slope. Five locations along the contour of each landscape position and at distance of 20 to 30 m were located and soil samples taken at two depths (0 to 20 cm and 20 to 40 cm). The soils were analyzed for pH, available P, texture, and exchangeable bases. Lunnyu patches on chromic lixisol and mollic gleysols had higher pH, P, sand, clay and silt compared to those on plinthic ferralsols and petrifferic lixisol. Neither of the soil properties was influenced by landscape position. Soil pH, Ca, Mg, and K were higher in topsoil compared to subsoil. Neither slope position nor the type of lunnyu has showed consistent differences in all the soil properties. Results suggest a pedological explanation in which pH and texture could influence occurrence of the lunnyu soils. We recommend further studies of the pedological properties of the soils and other trace elements that this study has not investigated.